2022
DOI: 10.5501/wjv.v11.i1.73
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking hospital psychiatry in Italy in light of COVID-19 experience

Abstract: BACKGROUND Italy retains a distinctive organization of mental health services according to a community-based model of care with a multidisciplinary team serving a well-defined catchment area under the coordination of the local department of mental health. The coronavirus disease 2019 (COVID-19) pandemic is forcing Italian mental health services to develop new organizational strategies at all levels of care in order to face the associated challenges. AIM To explore facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…This last data could indicate a potential marginalization of immigrant groups who have less access to care, as reported by some authors ( 69 ). Our regression model highlighted the outcomes more frequently associated with UPCs during COVID-19 period: referral to outpatient service from UPC in ER and home care from UPC in CMHS, neither indicating hospitalization, which was drastically reduced during the first months after pandemic outbreak ( 70 ). In any case, as observed by an author ( 71 ), we will appreciate the real impact and consequences of the COVID-19 pandemic on mental health of the general population only in future.…”
Section: Discussionmentioning
confidence: 96%
“…This last data could indicate a potential marginalization of immigrant groups who have less access to care, as reported by some authors ( 69 ). Our regression model highlighted the outcomes more frequently associated with UPCs during COVID-19 period: referral to outpatient service from UPC in ER and home care from UPC in CMHS, neither indicating hospitalization, which was drastically reduced during the first months after pandemic outbreak ( 70 ). In any case, as observed by an author ( 71 ), we will appreciate the real impact and consequences of the COVID-19 pandemic on mental health of the general population only in future.…”
Section: Discussionmentioning
confidence: 96%
“…The improvement in coping strategy of severe psychiatric patients in critical periods 31,32 and more similar condition to the general populations could improve the mental health of the more severe patients, along with the increase of patients and family's support. 18 Moreover, the reduction of Emergency Room (ER) admissions for psychiatric disorders 3,4,33 in the lockdown period attributable to the fear of the contagion, 34 especially in older people, 35 could also delay the diagnosis of new onset psychiatric disorders. A multicen-ter study carried out in Italian ERs, 35 in line with this hypothesis, found a 50% reduction of admissions also for non psychiatric patients, especially for less severe reasons (white and green codes) while no changes were found for the most severe reasons (red codes).…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen percent of psychiatric ward in Lombardy (that in Italy are positioned in the general hospitals) were temporary converted in intensive and nonintensive non psychiatric care COVID unit. 6,13,18 More specifically, in the province of Como, the psychiatric ward in the Hospital of Cantù was temporary closed, with reduction of the beds in the entire province, and consequently, along with the fear of the contagion, a reduction of availability for new admissions. 12 In fact, in line with other studies carried out in Italy; 6,15,17 we found a significant reduction in voluntary admissions while the number of compulsory admissions remained stable; that mean an "increased threshold" for inpatient admissions and only the more severe patients keep being admitted to the psychiatric wards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One wonders whether intervening in these cases necessarily corresponds to a forced hospitalization in a psychiatric facility or if it was possible to carry out other types of treatment, for example by carrying out a home intervention over a medium-short period (days or a few weeks). The forced hospitalization is a tool experienced in a violent way by those who are subjected to it, and often the patient's rehabilitation measures do not allow the patient to nd a home in his or her family that can accommodate them once hospitalization is over [39,40,41] The hope for the future would be to be able to nourish and nurture a global model of community mental health intervention [42] by training professional staff in a holistic conception of mental distress and educating society to request and integrate psychiatric interventions [43] with support from the third sector, ascertaining the continuity of care in the family and community after discharge from hospitals.…”
Section: Discussionmentioning
confidence: 99%